Shifts and equivalencies of idiomatic expressions in novel “The Name of Rose” - Aliurridha Aliurridha; Teguh Setiawan (Journal on English as a Foreign Language, 2019)
This research aims to find the translation shifts and the equivalencies of idiomatic expressions. Data in this research were idiomatic expressions found in the novel “The Name of the Rose” and its translation. The method of data collection used reading and recording technique with researchers as the instrument along with some parameters of idiomatic expressions that were proposed by experts.  In analyzing the data, this research used the referential and translational method with structural and componential analysis. The result found that there was another category shift that cannot be explained by the contemporary theory of translation shift. It happens because the contemporary theory of translation shift only focuses on the micro-linguistic level. This type of shift occurred in idiomatic expression due to the lack of equivalencies of the source text (ST) and target text (TT) whether in the grammatical system or the cultural difference. This research suggests that the theory translation shifts should be provided by semantic, pragmatic, discourse, and intercultural knowledge to bridge a gap between the two languages.